Analysis Of Factors Associated With Employee Performance At The Health Office Of Southwest Papua Province In 2026 - Linda Margared Antaribaba; Muhammad Akbar Nurdin; Arius Togodly; Yacob Ruru; Septevanus Rantetoding; Dolfinus Bouway (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze factors associated with employee performance at the Health Office of Southwest Papua Province in 2026. This research used an analytical quantitative design with a cross-sectional approach. The population consisted of all employees totaling 97 respondents, selected using a total sampling technique. Data were collected using structured questionnaires based on each research variable. Data analysis was conducted using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using logistic regression. The results showed that most respondents had good performance (61.9%), good leadership (57.7%), high work motivation (60.8%), good competence (63.9%), and a supportive work environment (59.8%). However, the majority of respondents experienced a heavy workload (53.6%). Bivariate analysis revealed significant relationships between leadership (p=0.003), work motivation (p=0.001), competence (p=0.002), work environment (p=0.003), and workload (p=0.004) with employee performance. The multivariate analysis indicated that work motivation was the most dominant factor associated with employee performance, with an Odds Ratio (OR) of 3.35. This implies that employees with high work motivation are more likely to have good performance compared to those with low motivation. In conclusion, all independent variables were significantly related to employee performance, with work motivation as the most dominant factor. It is recommended to improve employee motivation through incentives, career development, and better workload management.